Physical and economic efficiency of water use in the river basin: implications for efficient water management - Cai, Ximing; Ringler, Claudia; Rosegrant, Mark W. (American Geophysical Union, 2003)
With growing water scarcity and increasing competition across water‐using sectors, the need for water savings and more efficient water use has increased in importance in water resources management. Improvement in the physical efficiency of water use is related to water conservation through increasing the fraction of water beneficially used over water applied, while enhancing economic efficiency is a broader concept, seeking the highest economic value of water use through both physical and managerial measures. Physical and economic efficiency measures are both useful indicators for water management at the irrigation system and river basin level. However, the relationship between physical efficiency and economic efficiency is not always clear, and the values of these measures may indicate different directions for water policy and investments in irrigation. Open research questions include, for example, the following: How does the change in responsiveness of water allocation and irrigation technology to economic incentives affect physical and economic irrigation efficiency? What is the impact of a change in irrigation system efficiency on basin physical and economic efficiency? How do changes in water withdrawals affect basin physical and economic efficiency under a given water requirement? To explore these issues, an integrated economic‐hydrologic river basin model is applied to the Maipo River Basin in Chile. A series of modeling scenarios is defined, and policy implications based on changes in physical and economic efficiencies for basin‐wide irrigation water management are analyzed.